Determinan Perubahan Anggaran Belanja Modal Pemerintah Daerah Kota di Indonesia - Akmalia Putri; Syukriy Abdullah; Suparno Suparno; Gamal Batara (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2024)
The purpose of this study was to examine the effect of changes in the local own revenue budget and revenue sharing funds budget on changes in the capital expenditure budget in local governments in Indonesia. The selected sample was 76 local governments. The data used is secondary data sourced from the website of the Directorate General of Fiscal Balance (DJPK) of the Ministry of Finance of the Republic of Indonesia in the form of the initial budget and the revised budget in the 2019-2020 budget year. Data analysis used a multiple linear regression model with the help of SPSS 26 software. The results of the study showed that each variable of changes in the local own revenue budget and revenue sharing funds budget had a positive effect on the changes in the capital expenditure budget. These results show the phenomenon that local revenue and revenue sharing funds are very important in financing capital expenditures in local governments in Indonesia, including during the COVID-19 Pandemic in 2020.